Stereological study on the numerical plasticity of myelinated fibers and oligodendrocytes in the rat spinal cord with painful diabetic neuropathy. Issue 4 (4th March 2020) - Lin, Jing-yan; Zhu, Na; He, Yi-na; Xu, Bo-lin; Peng, Bin
Abstract : Painful diabetic neuropathy may associate with nerve morphological plasticity in both peripheral and central nervous system. The aim of this study was to determine numerical changes of myelinated fibers in the spinothalamic tract region and oligodendrocytes in the spinal dorsal horn of rats with painful diabetic neuropathy and the effects of metformin on the above changes. Male Sprague–Dawley rats were randomly allocated into the control group ( n = 7), the painful diabetic neuropathy group ( n = 6) and the painful diabetic neuropathy treated with metformin group (the PDN + M group, n = 7), respectively. Twenty-eight days after medication, numbers of myelinated fibers in the spinothalamic tract and oligodendrocytes in the spinal dorsal horn were estimated by the optical disector (a stereological technique). Compared to the control group, number of myelinated fibers in the spinothalamic tract increased significantly in the painful diabetic neuropathy and PDN + M group, compared to the painful diabetic neuropathy group, number of myelinated fibers decreased in the PDN + M group ( P < 0.05). As the oligodendrocyte in the spinal dorsal horn was considered, its number increased significantly in the painful diabetic neuropathy group compared to the control and the PDN + M group ( P < 0.05), there was no significant difference between the control and the PDN + M group ( P > 0.05). Our results indicate that painful diabetic neuropathy is associated with a serial of morphometric plasticity in the rat spinal cord including the numerical increase of the myelinated fibers in the spinothalamic tract and the oligodendrocytes in the spinal dorsal horn. The analgesic effect of metformin against painful diabetic neuropathy might be related to its adverse effects on the above morphometric plasticity.